Decipher hydrological-ROS-mineral-microbe geochemical interaction and groundwater table fluctuation governing chain-length dependent PFAS evolution - Wenbing Wang; Zhaojing Yu; Qifeng Fan; Haohao Hu; Chunyang Li; Yongkang Wei; Hui Li (Water Research, 2026)

Carboxymethyl chitosan-stabilized Cu2O nanocomposites integrated into biomimetic 3D nanofibrous scaffolds for infected wound microenvironment modulation - Nan Jiang; Xinlan Wang; Junjie Shen; Zengxiao Cai; Yuxiang Yao; Tanlong Liu; Youjing He; Zhirang Hu; Zhiyong Yan; Linpeng Fan; Anlin Yin; Chunyang Wang; et al. (Carbohydrate Polymers, 2026)

A novel strategy for intervertebral disc degeneration: An SS31-modified pH-sensitive hydrogel for sustained release of asiatic acid - Chunyang Fan; Ying Zhu; Yao Zhang; Linsheng Liu; Wei He; Yongkang Deng; Xiexing Wu; Dechun Geng; Haiqing Mao (Chemical Engineering Journal, 2026)

Mixed-dimensional COF membrane towards fast organic solvent nanofiltration - Fenglong Dai; Tingyuan Wang; Yanan Liu; Xiaocui Wei; Fu Zhao; Enshen Shi; Yigui Du; Chunjia Wang; Shijie Liu; Chunyang Fan; Yuhan Wang; Zhongyi Jiang (Chemical Engineering Journal, 2026)

Eosinophil cationic protein-driven type 2 inflammation impairs olfactory function in a murine model - Zhong Zheng; Liufeiyan Fan; Haofei Bai; Silyu Jing; Chunyang Zhang; Yubin Lai; Min Xu; Jian Wang; Tao Xue; Dingjun Zha; Fuquan Chen (Inflammation Research, 2026)

Innovative continuous-flow pyrrhotite-persulphate micro-nano catalytic system for sulfamethoxazole and Cr(VI) co-contaminated groundwater: Concentration-dependent mechanisms and plume evolution prediction - Chunyang Li; Qifeng Fan; Hui Li; Yongkang Wei; Wenbing Wang (Journal of Environmental Chemical Engineering, 2026)

Continuous-flow pyrrhotite-persulphate system for synchronous groundwater sulfamethoxazole-hexavalent chromium removal under different saturation conditions - Chunyang Li; Qifeng Fan; Hui Li; Yongkang Wei; Wenbing Wang (Environmental Pollution, 2026)

Hydrothermal alchemy: Iron‑sulfur minerals unlock the door to optimal PFAS wastewater low temperature treatment with enhanced efficacy - Wenbing Wang; Haohao Hu; Chunyang Li; Xinlei Ren; Qifeng Fan; Yongkang Wei; ZhaoJing Yu; Hui Li (Chemical Engineering Journal, 2026)

Fracture-mediated transport and bio-mineral synergistic attenuation of PFOA plumes: Implications prediction for reactive remediation in heterogeneous field coupling with various groundwater environment - Wenbing Wang; Yongkang Wei; Chunyang Li; Qifeng Fan; Haohao Hu; Hui Li (Journal of Hazardous Materials, 2025)

Recent research progress of methane dry reforming to syngas - Yan Wang; Rui Li; Chunyang Zeng; Wenjuan Sun; Hui Fan; Qingxiang Ma; Tian-Sheng Zhao (Fuel, 2025)

(Z)-Ligustilide alleviates intervertebral disc degeneration by suppressing nucleus pulposus cell pyroptosis via Atg5/NLRP3 axis - Jiale Wang; Chunyang Fan; Yao Zhang; Di Hua; Zhongwei Ji; Wei He; Yongkang Deng; Dechun Geng; Xiexing Wu; Haiqing Mao (Science China Life Sciences, 2025)

Simulation study on damage behavior of a shallow-buried Foundation bridge under combined action of flood scouring and heavy vehicle load - Tong Wu; Gangping Fan; Chuandong Dou; Xing Li; Chunyang Dou; Jian Che; Tianzhuo Wang; Jincheng Rao (Ocean Engineering, 2025)

Cyclodextrin tuned interlayer spacing in covalent organic framework membranes for efficient dye/salt separation - Xiaocui Wei; Yanan Liu; Jianghao Huang; Zongmei Li; Fu Zhao; Zhao Zhang; Tingyuan Wang; Chunyang Fan; Yuhan Yang; Zhongyi Jiang (Desalination, 2025)

Exploring spatiotemporal characteristics of ride-hailing ridership connecting with metro stations: A comparative analysis of holidays, weekdays, and weekends - Zhitao Li; Fan Gao; Jingjing Hao; Jian Liang; Chunyang Han; Jinjun Tang (Journal of Transport Geography, 2025)

Iron (hydr)oxide minerals-microbe interaction associated retention capacity boost and reaction rate fluctuation for perfluorooctanoic acid in an in-situ iron-based and microbe-based sustained-release system - Chunyang Li; Qifeng Fan; Tiantian Gong; Hui Li; Yongkang Wei; Wenbing Wang (Journal of Cleaner Production, 2024)

Hypoxia preconditioning increases Notch1 activity by regulating DNA methylation in vitro and in vivo - Zhehan Chang; Qi Liu; Peijia Fan; Wenqiang Xu; Yabin Xie; Kerui Gong; Chunyang Zhang; Zhijun Zhao; Kai Sun; Guo Shao (Molecular Biology Reports, 2024)

Perfluorooctanoic acid transport and fate difference driven by iron-sulfide minerals transformation interacting with different types of groundwater - Yongkang Wei; Wenbing Wang; Qianling Dong; Qifeng Fan; Meng Zhang; Chunyang Li; Hui Li (Journal of Hazardous Materials, 2024)

The impact of shared mobility on metro ridership: The non-linear effects of bike-sharing and ride-hailing services - Fan Gao; Sylvia Y. He; Chunyang Han; Jian Liang (Travel Behaviour and Society, 2024)

Perfluorooctanoic acid efficient chain reaction degradation in multifunctional iron-sulfur mineral augmentation geobiochemical remediation system - Qifeng Fan; Meng Zhang; Yiming Liu; Wenbing Wang; Chunyang Li; Yongkang Wei; Hui Li (Chemical Engineering Journal, 2024)

Is cryoablation still suitable for advanced non-small cell lung cancer after failure of first-line chemotherapy? A multicenter, prospective, randomized-controlled trial of eighty-seven patients - Yu Chen; Xueni Fang; Dan Wang; Quanwang Li; Kerui Zhang; Yuan Li; Jinghua Li; Haoyue Pang; Zhiqiang Cheng; Chunyang Zhang; Caiyun Zhang; Wuwei Yang; et al. (Cryobiology, 2024)

Perfect cooperative pest control via nano-pesticide and natural predator: High predation selectivity and negligible toxicity toward predatory stinkbug - Shangyuan Wu; Qinhong Jiang; Zhilin Xia; Zhirong Sun; Qing Mu; Chunyang Huang; Fan Song; Meizhen Yin; Jie Shen; Hu Li; Shuo Yan (Chemosphere, 2024)

Superb green cycling strategies for microbe-Fe0 neural network-type interaction: Harnessing eight key genes encoding enzymes and mineral transformations to efficiently treat PFOA - Wenbing Wang; Qifeng Fan; Tiantian Gong; Meng Zhang; Chunyang Li; Yunhui Zhang; Hui Li (Journal of Hazardous Materials, 2024)

Electrochemical hydrogen Compression: Module design and membrane development - Zhong Gao; Chunyang Fan; Zhuoyu Yin; Sijia Wang; Leilang Zhang; Na Xing; Shiyi Zhu; Zengguang Yao; Hong Wu; Zhongyi Jiang (Chemical Engineering Journal, 2024)

Comprehensive analysis of MAPK gene family in upland cotton (Gossypium hirsutum) and functional characterization of GhMPK31 in regulating defense response to insect infestation - Fuqiu Wang; Sijia Liang; Guanying Wang; Qiongqiong Wang; Zhongping Xu; Bo Li; Chunyang Fu; Yibo Fan; Tianyu Hu; Muna Alariqi; Amjad Hussain; Jinglin Cao; et al. (Plant Cell Reports, 2024)
Key message The transcriptomic, phenotypic and metabolomic analysis of transgenic plants overexpressing GhMPK31 in upland cotton revealed the regulation of H 2 O 2 burst and the synthesis of defensive metabolites by GhMPK31 . Abstract Mitogen-activated protein kinases (MAPKs) are a crucial class of protein kinases, which play an essential role in various biological processes in plants. Upland cotton ( G. hirsutum ) is the most widely cultivated cotton species with high economic value. To gain a better understanding of the role of the MAPK gene family, we conducted a comprehensive analysis of the MAPK gene family in cotton. In this study, a total of 55 GhMPK genes were identified from the whole genome of G. hirsutum . Through an investigation of the expression patterns under diverse stress conditions, we discovered that the majority of GhMPK family members demonstrated robust responses to abiotic stress, pathogen stress and pest stress. Furthermore, the overexpression of GhMPK31 in cotton leaves led to a hypersensitive response (HR)-like cell death phenotype and impaired the defense capability of cotton against herbivorous insects. Transcriptome and metabolomics data analysis showed that overexpression of GhMPK31 enhanced the expression of H 2 O 2 -related genes and reduced the accumulation of defensive related metabolites. The direct evidence of GhMPK31 interacting with GhRBOHB (H 2 O 2 -generating protein) were found by Y2H, BiFC, and LCI. Therefore, we propose that the increase of H 2 O 2 content caused by overexpression of GhMPK31 resulted in HR-like cell death in cotton leaves while reducing the accumulation of defensive metabolites, ultimately leading to a decrease in the defense ability of cotton against herbivorous insects. This study provides valuable insights into the function of MAPK genes in plant resistance to herbivorous insects.

Seaward alteration of arsenic mobilization mechanisms based on fine-scale measurements in Pearl River estuarine sediments - Chunyang Zhou; Wei Lin; Zhaokui Ni; Fuqiang Fan; Yue Dong; Yue Gao; Willy Baeyens; Shengrui Wang (Journal of Hazardous Materials, 2024)

Analyzing spatiotemporal distribution patterns of metro ridership: Comparison between common-class and business-class carriage service - Fan Gao; Chunyang Han; Linchuan Yang; Jian Liang; Xuan He; Fan Li (Journal of Transport Geography, 2024)

Shifts in the high-resolution spatial distribution of dissolved N2O and the underlying microbial communities and processes in the Pearl River Estuary - Xiang Cheng; Yue Dong; Fuqiang Fan; Shangbin Xiao; Jia Liu; Shengrui Wang; Wei Lin; Chunyang Zhou (Water Research, 2023)

Recognizing the variation of bioavailable organic phosphorus in sediment and its significance between high and low risk periods for algal blooms in Lake Erhai - Jia Pu; Shengrui Wang; Fuqiang Fan; Chunyang Zhou; Zhezhe Liu (Water Research, 2023)

Generation of a selectable marker free, highly expressed single copy locus as landing pad for transgene stacking in sugarcane - Yang Zhao; Jae Y. Kim; Ratna Karan; Je H. Jung; Bhuvan Pathak; Bruce Williamson; Baskaran Kannan; Duoduo Wang; Chunyang Fan; Wenjin Yu; Shujie Dong; Vibha Srivastava; et al. (Plant Molecular Biology, 2019)

Economic evaluation of health losses from air pollution in Beijing, China - Xiaoli Zhao; Xueying Yu; Ying Wang; Chunyang Fan (Environmental Science and Pollution Research, 2016)